Effects of labor motivation in poultry production - M do CB de Alencar (Revista Brasileira de Ciência Avícola, 2007)
Broiler production is a significant economic activity in Brazil, and employs a large number of stockpeople in the integration process. Considering that the stockperson's perception may lead to better performance of his/her tasks and flock handling, this study aimed at verifying possible interactions between poultry productivity and stockperson's perception, emotions, and motivation. The study methodology considered two aspects: qualitative analysis, using Ergonomic Work Analysis, with observational method, and by applying a questionnaire and interview, and classification of the answers into positive relationship and "affection" to the job or negative relationship and "disaffection" to the job; and quantitative analysis, applying the Test of Hypothesis for Comparison of Means both for total flock mortality and Weight Equivalent Index data. Qualitative results showed that the stockpeople were aware that the housing environment causes specific health symptoms, as well as they presented different responses as to flock handling. Quantitative data showed a correlation between reduction of total flock mortality and positive relationship towards the broilers and "affection" to the job, whereas no statistical evidence that the same individuals influenced broiler Weight Equivalent Index was detected.